Peran Stres Kerja dalam Memediasi Pengaruh Beban Kerja terhadap Kepuasan Kerja pada Perawat RSU Prima Medika - Anak Agung Istri Nadya Paramitha; I Gusti Ayu Dewi Adnyani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The business world in the service sector, such as hospitals, is experiencing competition in providing health services to its patients. This study aims to analyze the role of work stress in mediating the influence of workload on job satisfaction among nurses at RSU Prima Medika. This study used a sample of 117 nurses using the proportionate random sampling method. Data collection was carried out using a survey method with questionnaire and interview techniques. The collected data was then analyzed using path analysis techniques, classical assumption tests, and mediation role testing. The research results show that workload has a negative and significant effect on job satisfaction. Workload has a positive and significant effect on work stress. Job stress has a negative and significant effect on job satisfaction. Job stress mediates partially (competitive partial mediation) the effect of workload on job satisfaction. The results of this research can contribute to the two-factor theory and be a consideration for RSU Prima Medika in increasing the job satisfaction of its nurses.